EFFECTS OF VARIOUS SOIL ENVIRONMENTAL STRESSES ON THE OCCURRENCE, DISTRIBUTION AND EFFECTIVENESS OF VA MYCORRHIZAE - A.G. KHAN (SEAMEO BIOTROP, 1995)
The vesicular - arbuscular (VA) mycorrhizal fungi are geographically ubiquitous soil inhabitants and form universal symbiotic relationship with plants from every phylum. These fungi link host plants with host soils and their biota in the mycorrhizosphere and play an important role in plant health, productivity and soil structure. Although VA mycorrhizal fungi do not show any host specificity, there is increasing evidence that various climatic and edaphic environmental factors such as land use and management practices, physical, chemical and biological properties of host soils and host plant characteristics influence their occurrence, taxonomic distribution and effectiveness. The interaction of these factors with vesicular-arbuscular mycorrhizae (VAM) is poorly understood except in a few cases. It is now very clear that VA mycorrhizal associations are ecologically significant factors that require more attention than previously accorded. This paper discusses the occurrence, distribution and significance of VAM in environmentally stressed soil conditions that limit plant growth such as drought, waterlogging and salinity. Key words: Mycorrhizas/Environmental factors/Waterlogging/Soil salinity/Growth development stages/ Inoculum.